Molecular Docking Studies of Natural Phenolic Compound and Derivates with Phospholipase A2 - Pablo Henrique Delmondes; Ricardo Stefani (Orbital: The Electronic Journal of Chemistry, 2018)
The enzyme phospholipase A2 (PLA2) catalyzes the conversion of membrane phospholipids in the inflammatory mediators, such as prostaglandins and leukotrienes. Because of this role, substances with inhibitory activity of PLA2 enzyme, has gained prominence in the scientific community like possible anti-inflammatory. Several studies have shown that phenolic compounds such as flavonoids, phenolic acids and other, has, among various biological activities, anti-inflammatory activity by inhibition of the enzyme PLA2. Based on this context, this study aimed to conduct a molecular docking study of various natural phenolic compounds and some of their derivatives forward to the enzyme PLA2. The crystallographic structure of PLA 2 was obtained from Target Database Protein Data Bank [PDB ID: 1KPM] and the ligands were obtained from PubChem Database. The docking was performed using the AutoDock 4.0 software. It was observed that among the phenolic compounds included in the study, those with better interaction with the enzyme were rosmarinic acid 3'-O-beta-glucoside, 4-nerolidylcatechol, rosmarinic acid methyl ester, quercetin 3-O-malonylglucoside, quercetin pentaacetate and rosmarinic acid, respectively. The present study provides a better understanding of the inhibition of PLA2 by phenolic compounds, which may contribute to the development of new anti-inflammatories.DOI: http://dx.doi.org/10.17807/orbital.v10i6.981